2020
DOI: 10.3390/ma13092086
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Hydroxyapatite Inhibits Bisphosphonate Toxicity to the Oral Mucosa In Vitro

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a side effect of bisphosphonate therapy, characterised by exposed necrotic bone. The soft tissues of the oral mucosa no longer provide a protective barrier and MRONJ patients experience pain, infections and difficulties eating. We hypothesised that hydroxyapatite (Ca5(PO4)3(OH)) could reduce bisphosphonate concentrations and protect the oral mucosa by exploiting bisphosphonate’s calcium binding affinity. The effect of zoledronic acid (ZA) and pamidronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…The situation changes when the final products are tested on primary dermal and gingival fibroblasts, respectively, when cytotoxic effects were recorded in a dose-dependent manner, dermal cells being more sensitive compared to gingival ones. Similar results were reported by Bullock et al in 2020 who revealed that oral fibroblasts were more sensitive to external agents than oral keratinocytes [ 89 ]. We may assume that because of stem-like features and higher proliferation rates keratinocytes exhibit superior resistance to external agents compared to fibroblasts.…”
Section: Resultssupporting
confidence: 90%
“…The situation changes when the final products are tested on primary dermal and gingival fibroblasts, respectively, when cytotoxic effects were recorded in a dose-dependent manner, dermal cells being more sensitive compared to gingival ones. Similar results were reported by Bullock et al in 2020 who revealed that oral fibroblasts were more sensitive to external agents than oral keratinocytes [ 89 ]. We may assume that because of stem-like features and higher proliferation rates keratinocytes exhibit superior resistance to external agents compared to fibroblasts.…”
Section: Resultssupporting
confidence: 90%
“…To examine healthy mucosa, models were cultured in standard media and epithelia allowed to stratify before BP treatment. PA treatment has been demonstrated to reduce epithelial thickness in studies from our group, and Kim et al [ 58 , 61 ]. Kim et al witnessed a thinner basal layer and intact keratinised layers, and suggested that BP treatment may speed up keratinocyte differentiation.…”
Section: Bisphosphonatesmentioning
confidence: 72%
“…PA has been demonstrated to be toxic to human oral fibroblasts from 24 h of administration, with lower concentrations causing toxicity after longer the treatment length. For example an IC 50 of 43 μM was generated at 72 h of treatment in work from our group [ 61 ], while at 96 h, Kim et al demonstrated a 10 μM PA treatment significantly reduced viability [ 58 ]. There is some variability within the results, however the toxic effect of PA at physiologically relevant concentrations and over short time scales is clear.…”
Section: Bisphosphonatesmentioning
confidence: 99%
See 2 more Smart Citations